Material Preparation and Geotechnical Properties of Transparent Cemented Soil for Physical Modeling - Leng, Xianlun; Wang, Chuan; Pang, Rong; Sheng, Qian; Chen, Jian (Frontiers in Materials, 2021)
The preparation of transparent materials suitable for simulating different rock and soil masses is the foundation for image-based physical modeling tests in studying deformation and failure mechanisms in geotechnical media. A transparent cemented soil (TCS) with similar geotechnical properties of natural soil and soft rock was prepared using fused quartz as the skeleton, hydrophobic fumed silica powder as the cement and mixed mineral oil of 15# white oil and n-dodecane as the pore fluid. Eleven groups of TCS samples with different shear strengths were synthesized by adjusting the content or mass ratio of the cement and particle size or gradation of the skeleton. Contrasting tests of unconsolidated-undrained triaxial compression were carried out and the mechanical characteristics of TCS were analyzed, showing that the stress-strain relationship, shear strength and failure mode of TCS are similar to those of natural soil. The mechanical parameters of TCS undergo complex variation with the factors, and the mesoscopic mechanism of the changes therein was revealed with the help of optical microscope photos. The similarity ratio of TCS to soft rock was derived according to geometries and stress conditions of laboratory model tests, demonstrating the feasibility of using TCS as similar materials to soft rock. Moreover, empirical formulas for the change of shear strength parameters with the factors were fitted to facilitate the preparation of TCS with target shear strength in the future. The findings can provide a basis for preparing transparent similar materials to natural soil and soft rock in physical modeling tests.